Epipericardial fat necrosis as cause of chest pain in patient after heart transplantation. Issue 5 (24th January 2020) - Cafezeiro, Caio Rebouças Fonseca; Lopes, Mariana Pezzute; Silva, Caio Tavares; Ávila, Mônica Samuel; Seguro, Luis Fernando B. C.; Mangini, Sandrigo; Campos, Iáscara Wozniak; Gaiotto, Fábio A.; Marcondes‐Braga, Fabiana G.; Bacal, Fernando
Abstract : Epipericardial fat necrosis is an uncommon clinical condition of unknown etiology. It typically presents as acute pleuritic chest pain and should be differentiated from acute pulmonary embolism and acute coronary syndrome. This condition is diagnosed by characteristic chest computed tomography findings of an ovoid mediastinal fatty lesion with intrinsic and surrounding soft‐tissue stranding. Treatment of epipericardial fat necrosis includes the administration of anti‐inflammatory agents, and symptoms usually resolve within a few days after treatment initiation. This disease entity has rarely been reported since it was first described in 1957. Most current knowledge of epipericardial fat necrosis is based on case reports that describe this condition in previously healthy individuals. We present the case of a 39‐year‐old woman with a history of heart transplant, who presented with chest pain secondary to epipericardial fat necrosis. Serial computed tomography revealed lesion resolution after appropriate treatment. Abstract : This is a case report of a 39‐year‐old woman, submitted to heart transplantation, who presents with epipericardial fat necrosis successfully treated with low‐dose oral corticosteroid therapy.